Voluntary zakat disclosure of Islamic banks in Malaysia / Salehah Zafirah Zulkepli - Zulkepli, Salehah Zafirah (Universiti Teknologi MARA Selangor, 2023)
The primary objective of this paper is to scrutinize the voluntary zakat disclosure practices and the methods employed for zakat computation within Islamic banks in Malaysia. Additionally, the study aims to explore the relationship between zakat disclosure and specific characteristics, including the amount of zakat, the size of the bank, and profitability. The methodology involves an initial content analysis of the annual reports of 17 Islamic banks in Malaysia. The findings highlight the prevalent use of the Adjusted Growth Method as the primary approach to zakat computation by Islamic banks. Furthermore, certain banks exhibit a more comprehensive disclosure of zakat information, both financial and non-financial, within the Shariah Committee Report and the Notes to the Financial Statements. Upon analysis, the results indicate a positive and significant relationship between the amount of zakat and zakat disclosure. These findings carry crucial implications for Islamic banks, emphasizing the need to enhance transparency, accountability, and comparability in their disclosure practices. Such improvements not only have the potential to positively impact financial performance but also contribute to building the reputation of Islamic banks among various stakeholders.